Entrepreneurial Orientation and Strategy Channel Distribution to Success Entrepreneurship with Superiority Compete as Mediation on Center Coffee Muria Kudus - Setiyanto, Aji; Lusianti, Dina; Faidah, Faridhatun (Journal of Applied Business and Technology, 2024)
This study analyzes the influence of entrepreneurial orientation and distribution channel strategy on entrepreneurial success with competitive advantage as mediation in the Muria coffee center Kudus, Central Java, Indonesia. This research is descriptive statistically by testing hypotheses. The sample was 110 business actors. Sampling technique using Purposive Sampling The data collection used in this study is a questionnaire method. Test Instruments use validity tests, reliability tests, and normality tests. Analysis of data used Structural Equation Modeling operated through the AMOS program. The results are entrepreneurial orientation does not have a significant direct effect on competitive advantage. Distribution channel strategy directly affects competitive advantage, and entrepreneurial orientation has no significant direct effect on entrepreneurial success. Distribution channel strategy has a direct effect on entrepreneurial success. Competitive advantage has a direct effect on entrepreneurial success. Competitive advantage can mediate the influence of entrepreneurial orientation on entrepreneurial success, and competitive advantage can mediate the influence of distribution channel strategy on entrepreneurial success as partial mediation.